1995
DOI: 10.1002/ajim.4700270413
|View full text |Cite
|
Sign up to set email alerts
|

Chronology of asbestos cancer discoveries: Experimental studies of the saranac laboratory

Abstract: This commentary challenges a recently published perception that Dr. Le Roy Upson Gardner had not actually discovered in 1942 that inhaled chrysotile fibers could induce malignant neoplasia in mice. The handwritten laboratory notes and some of Dr. Gardner's slides have recently been found. They verify that the tumors he saw in the mice included truly malignant neoplasms. Gardner had by then also accumulated 11 cases of human lung cancer (two mesotheliomas) derived from Quebec asbestos miners and millers. An inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…For example, he justi®ed his study on the basis of the scepticism of Cartier, Lanza and Vorwald, whose partisanship would only have been known to those familiar with the ®eld. Their roles in the history of asbestos were not to be publicized for some time yet [Schepers, 1995]. Having attended the 1952 Louvain symposium, he would have been aware of his peers' opinion that the carcinogenicity of asbestos was beyond discussion.…”
Section: Turner's Invitation To Doll To Survey Their Mortality Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, he justi®ed his study on the basis of the scepticism of Cartier, Lanza and Vorwald, whose partisanship would only have been known to those familiar with the ®eld. Their roles in the history of asbestos were not to be publicized for some time yet [Schepers, 1995]. Having attended the 1952 Louvain symposium, he would have been aware of his peers' opinion that the carcinogenicity of asbestos was beyond discussion.…”
Section: Turner's Invitation To Doll To Survey Their Mortality Datamentioning
confidence: 99%
“…It was left to a turbulent South African government scientist visiting at the Saranac Laboratory in 1960, to disinter Gardner's disputed histopathological evidence for asbestos being tumorogenic, and to con®rm the malignant nature of the lung tumors [Schepers, 1995]. When Schepers informed his hosts of his discoveries, they promptly placed an embargo on the material to prevent publication.…”
Section: Experimental Pathology Datamentioning
confidence: 99%
“…Gardner's earlier experience, Vorwald [1952] sent a report to the Quebec Asbestos Mining Association giving an interim result of an experimental asbestos exposure study they had commissioned, that was ominous of a lung cancer hazard. The study was discontinued, Vorwald had his appointment terminated and the laboratory was to close [Schepers, 1995].…”
Section: Respiratory Malignancy Lung Cancermentioning
confidence: 99%
“…While this had not reached statistical significance, the researchers warned that the incidence of tumors had increased ominously in the most recently killed group of exposed animals. The QAMA had in the early 1940s received and suppressed a report of a similar study at that institute that had demonstrated asbestos to be tumorogenic [Schepers, 1995]. They sponsored a mortality study of its miners, which concluded that Quebec asbestos miners did not have a significantly higher death rate from ''lung cancer'' than comparable segments of the general population, and even contended that world-wide the experience of the asbestos exposed was not worse than that of the non-exposed [Braun and Truan, 1958].…”
Section: Health Of Quebec Miners After 1940mentioning
confidence: 99%